Undergraduate laboratory experiment on determination of total protein content in milk powder by moving reaction boundary titration. Issue 6 (2nd November 2018) - Luo, Anling; Zheng, Youli; Chen, Xinxin; Cong, Fengsong
ABSTRACT: Laboratory exercises focused on protein quantification are frequently conducted in traditional undergraduate biochemistry laboratory curriculum. The laboratory course described here is designed to provide students with experience in measurement of protein content in milk powder by moving reaction boundary titration (MRBT), a new rapid technique for total protein content determination in milk. In addition, this approach is weakly influenced by nonprotein nitrogen reagents such as melamine and urea. The course was done as three weekly laboratory exercises. First, students established a standard curve for milk protein concentration by MRBT method. Then, students investigated the influence of nonprotein nitrogen reagents on MRBT method. Finally, students made a comparison among three different protein quantification methods (MRBT, Biuret, and Kjeldahl method). From the experiments, students grasped the concept and advantages of MRBT and deepened the understanding of protein quantification. This course offer students the opportunity to be exposed to an advanced technique, which may have practical significance to their future study and work in the life science field. © 2018 International Union of Biochemistry and Molecular Biology, 46(6):644–651, 2018.